Analisis Perbandingan Brand Equity Samsung dan LG - Imam Arif Fikri (Journal of Sustainable Community Development (JSCD), 2021)
This research is quantitative study that aims to compare brand association, perceived quality, and brand loyalty to brand equity in Samsung and LG companies in the South Jakarta area. This research used 100 respondents as a sample with purposive sampling method. The analysis technique in this study uses the Independent Sample T Test using SPSS 26. The results of this study indicate that (1) Samsung Brand Association is superior to LG, (2) Samsung's Perceived Qualty is superior to LG, (3) Samsung's Brand Loyalty is superior to LG. superior to LG. Keywords: Brand Equity; Brand Association; Perceived Quality; Brand Loyalty